PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Eka Herlina, Shefty; Susilowati, Dwi; Moorcy, Nadi Hermadi (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2025)
The purpose of this research is to determine the effect of Current Ratio, Debt to Asset Ratio, Return on Asset, and Earning per Share partially on Stock Prices. The data used in this research is in the form of secondary data obtained through the internet. The data used is the financial statements of the telecommunication subsector company for the 2020-2023 period. The data analysis method uses multiple linear regression, the analysis results show that the Current Ratio and Earning Per Share variables have a positive and significant effect on the Stock Price, Debt to Asset Ratio has a positive and insignificant effect on the Stock Price, Return on Asset has a negative and significant effect on the Stock Price.